Development of Ludo Media in Mathematics Learning on Two-Dimentional Figure in Second Grade of Madrasah Ibtidaiyah - Inayati, Isna Nurul; Islamiyah, Urfiatul (Universitas Negeri Malang, 2024)
This research is motivated by the lack of innovation among educators in the development of learning media, as well as the teaching models used by teachers, which are still teacher-centered. This condition leads to students easily getting bored in learning, resulting in a decline in their interest and learning outcomes. To address this issue, the researcher developed Ludo media. This study employs a Research and Development (R&D) approach using the Borg and Gall model, which consists of 7 adjusted stages. The subjects of this research are students in class IIa of MI Al Ihsan Jeru Turen. Validity tests were conducted with experts and practitioners, followed by field trials with students. The results showed that the media expert 1 rated the media at 90%, categorized as